Late-stage diagnosis of HIV infection in Brazilian children: evidence from two national cohort studies - Alberto Novaes Ramos Jr; Luiza Harunari Matida; Carlos Henrique Alencar; Norman Hearst; Jorg Heukelbach (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
This study analyzed data from two consecutive retrospective cohort samples (1983 to 1998 and 1999 to 2002) of Brazilian children with AIDS (N = 1,758) through mother-to-child-transmission. Late-stage diagnosis (CDC category C) was investigated in relation to the following variables: year of birth, year of HIV diagnosis, and time periods related to changes in government treatment guidelines. Late-stage diagnosis occurred in 731 (41.6%) of cases and was more prevalent in infants under 12 months of age. The rate of late-stage diagnosis decreased from 48% to 36% between the two periods studied. We also observed a reduction in the proportion of late-stage diagnoses and the time lapse between HIV diagnosis and ART initiation. A significant association was found between timely diagnosis and having been born in recent years (OR = 0.62; p = 0.009) and year of HIV diagnosis (OR = 0.72; p = 0.002/OR = 0.62; p < 0.001). Infants under the age of 12 months were more likely to be diagnosed at a late stage than older children (OR = 1.70; p = 0.004). Despite advances, there is a need to improve the effectiveness of policies and programs focused on improving early diagnosis and management of HIV/AIDS.